Reframing The Right to Regulate Clause in The Indonesia-China Investment Agreement - Wailanduw, Gilbert Leonard (Institute for Law and Economics Studies, 2026)
This analysis focusing on reframing the right to regulate clause as a legal mechanism for balancing Indonesia’s regulatory autonomy with the protection of Chinese investors under the Indonesia-China investment framework. Although the 1994 Indonesia-China Bilateral Investment Treaty (BIT) was terminated in 2015, its survival clause continues to provide investment protection for a period of ten years. Using a normative legal approach, this analysis focusing on legitimate expectations; legal paradigm reorientation; and the application of principle non-discrimination. This analysis proving the reconstruction right to regulate clause in the BIT is a solution to end the conflict between investment protection and the domestic policy. The result of this analysis implying the shift of the clause from general to be more specific focusing on downstream policy as the new standard of the international investment focusing on Indonesia and China investment agreement.